VD_FINDINFO Décision / 2013 / 288 vom 27. März 2013 - VD Tribunal cantonal (2013)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, SÉQUESTREMESURE PROVISIONNELLE | 90 LCR, 197 al.1 CPP (CH), 263 al. 1 let. d CPP (CH)